Carcinogenesis of Vulvar Lesions: Morphology and Immunohistochemistry Evaluation. Issue 1 (January 2017) - Rivero, Raquel Camara; Garcia, Deborah; Hammes, Luciano Serpa; Cerski, Marcelle Reesink; Magno, Valentino; Kliemann, Lúcia Maria; Capp, Edison
Abstract : Objectives: The aim of the study was to assess the 2 pathways of vulvar carcinogenesis and correlate immunohistochemical expression of p53 with histopathological findings. Materials and Methods: This cross-sectional study included 76 cases. Patients were classified according to the 2004 International Society for the Study of Vulvovaginal Disease Terminology, followed by a review of clinical records and immunohistochemical staining for p53. Results: Fifteen cases were in the human papillomavirus (HPV)-associated pathway (12 cases of usual vulvar intraepithelial neoplasia [VIN] and 3 of warty squamous cell carcinoma [SCC]), and 13 cases were in the HPV-independent pathway (5 cases of differentiated VIN and 8 of keratinizing SCC). Significant differences in p53 expression were observed between the 2 pathways of carcinogenesis: in the lesions related to the HPV-independent pathway, the percentage of p53-positive cells was greater (>25%, p < .001), and the staining pattern was basal (extending into the middle layer) in differentiated VIN and diffuse or infiltrative in warty SCC ( p < 0.001). In the lesions HPV-associated pathway, p53 staining was less extensive (⩽10% of cells, p < 0.001) and followed basal pattern in usual VIN, whereas warty SCCs were negative for p53 ( p < 0.001). Conclusions: Unique patterns of histological appearance and p53 expression can separate vulvar lesions into 2 distinct pathways of carcinogenesis. We propose that p53 immunohistochemistry may be performed simultaneously with histopathological examination in all cases of VIN and vulvar SCC, because it would aid in definition of the pathway of carcinogenesis and thus enable better clinical follow-up of patients with these conditions. Abstract : p53 immunohistochemistry may be performed with histopathological examination in cases of vulvar intraepithelial neoplasia and vulvar squamous cell carcinoma to assist in definition of the carcinogenesis pathway.